1998
DOI: 10.1021/es970322b
|View full text |Cite
|
Sign up to set email alerts
|

Full-Scale Evaluation of In Situ Cometabolic Degradation of Trichloroethylene in Groundwater through Toluene Injection

Abstract: Groundwater contaminated with 500−1200 μg/L trichloroethylene (TCE) was treated in situ over a 410-day period by cometabolic biodegradation through injection of 7−13.4 mg/L toluene, oxygen, and hydrogen peroxide in groundwater circulated between two contaminated aquifers through two treatment wells located 10 m apart. One well pumped contaminated groundwater from the 8 m thick upper aquifer to the 5 m thick lower aquifer, while the other pumped contaminated water from the lower to the upper aquifers using flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
151
2
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(158 citation statements)
references
References 14 publications
3
151
2
2
Order By: Relevance
“…Indeed, TCE is considered to be a potentially serious threat to drinking water sources (26). Considering this, research that has focused on both anaerobic reductive dechlorination and aerobic degradation via cometabolism has been under development (25,33).…”
mentioning
confidence: 99%
“…Indeed, TCE is considered to be a potentially serious threat to drinking water sources (26). Considering this, research that has focused on both anaerobic reductive dechlorination and aerobic degradation via cometabolism has been under development (25,33).…”
mentioning
confidence: 99%
“…In oxic contaminated subsurface environments, TCE can be degraded by means of a cooxidation reaction catalyzed by microbial oxygenases such as ammonia monooxygenase (2), alkene monooxygenase (8,9), methane monooxygenase (12,23), propane monooxygenase (24), toluene dioxygenase (6,14,52), and toluene monooxygenase (11,33,48). Among these, TCE cooxidation by bacteria carrying toluene oxygenase pathways has been of particular interest in environmental microbiology, since studies have shown that aerobic TCE biodegradation is stimulated in situ when toluene is added (15,26).…”
mentioning
confidence: 99%
“…Instead of trying to disperse bacteria over large distances, investigators have chosen to create smaller, bioactive zones of <1 m (McCarty et al, 1998). It is feasible to distribute cells over these smaller distances and the injection of nutrients into smaller bioactive zones can be more carefully controlled than more widespread nutrient additions and therefore are more likely to support the injected microbes than the indigenous community.…”
mentioning
confidence: 99%